Composite Reliability 1975
DOI: 10.1520/stp32307s
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Special X-Ray Nondestructive Testing Technique for Monitoring Damage Zone Growth in Composite Laminates

Abstract: A modified X-ray nondestructive testing technique was used to study matrix cracks parallel to fibers and delaminations between plies in graphite-epoxy composite material. A tetrabromoethane (TBE) opaque additive applied at the source of the damage zones enhanced the flaw image. Center-slit specimens were fabricated from Modmor II/Narmco 5208 graphite-epoxy laminates with three different ply orientations. Tensile ramp and sawtooth cyclic loadings at different levels were applied to these specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Direct damage detection methods include, among others, X-ray, 3 gamma-ray radiography, 4 ultrasonic probes, laser ultrasound, 5,6 thermography, 7 and microwave electromagnetic imaging. 8 In addition, acoustic techniques such as low power impulse radar, acoustic emission, and elastic wave emitter-detector pairs are in use.…”
Section: Introductionmentioning
confidence: 99%
“…Direct damage detection methods include, among others, X-ray, 3 gamma-ray radiography, 4 ultrasonic probes, laser ultrasound, 5,6 thermography, 7 and microwave electromagnetic imaging. 8 In addition, acoustic techniques such as low power impulse radar, acoustic emission, and elastic wave emitter-detector pairs are in use.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several researchers have investigated the solid particle erosion behavior of polymer matrix composites and concluded that FRP material is prone to flow-induced wall-thinning due to erosion. [3][4][5][6] Various non-destructive evaluation (NDE) techniques have been studied to detect damage and cracks in composite materials such as X-ray 7 and gamma-ray radiography. 8 In addition, acoustic techniques such as ultrasonic probes, laser ultrasound, 9,10 low-power impulse radar, acoustic emission, and elastic wave emitter-detector pairs have been also used.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, thermography 11 and microwave electromagnetic imaging 12 have been employed to investigate the damage in composite structures. However, the available non-destructive testing (NDT) methods have difficulties associated with their application in the field, as reported for radiography-based techniques, 7,8 ultrasonic tomography 13 and for infrared thermography. 14 In addition, the available NDT methods have limitations with respect to area of coverage, large thickness, and interpretation of their measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Radiography technique is one of the oldest NDE techniques. 1,2 Radiography is a photographic record produced by the penetration of electromagnetic radiation such as X-rays and gamma rays through the inspected object onto a film or other media. However, radiographic methods require large and costly equipment and extensive safety measures against radiation hazards.…”
Section: Introductionmentioning
confidence: 99%